2012
DOI: 10.1029/2011wr011761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storm movement on flood peaks: Analysis framework based on characteristic timescales

Abstract: [1] The aim of this paper is to investigate, in general terms, the effects of storm movement on the resulting flood peaks, and the underlying process controls. For this purpose, we utilize a broad theoretical framework that uses characteristic time and space scales associated with stationary rainstorms as well as moving rainstorms. For a stationary rainstorm the characteristic timescales that govern the peak response include two intrinsic timescales of a catchment and one extrinsic timescale of a rainstorm. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 29 publications
3
33
1
Order By: Relevance
“…Zoccatelli et al (2011) showed that an upbasin (downbasin) velocity is associated to a decrease (increase) of flood peak with respect to an equivalent stationary storm. A finding which is often reported is that the effect of storm motion on flood peak is maximized when storm velocity has similar magnitude as the channel flow velocity (Singh, 1998;Seo et al, 2012). Moreover, we introduce a methodology to evaluate the impact of neglecting the storm velocity in flood modeling.…”
Section: Ruiz-villanueva Et Al: Extreme Flood Response To Short-dmentioning
confidence: 99%
See 2 more Smart Citations
“…Zoccatelli et al (2011) showed that an upbasin (downbasin) velocity is associated to a decrease (increase) of flood peak with respect to an equivalent stationary storm. A finding which is often reported is that the effect of storm motion on flood peak is maximized when storm velocity has similar magnitude as the channel flow velocity (Singh, 1998;Seo et al, 2012). Moreover, we introduce a methodology to evaluate the impact of neglecting the storm velocity in flood modeling.…”
Section: Ruiz-villanueva Et Al: Extreme Flood Response To Short-dmentioning
confidence: 99%
“…This originates a downbasin catchment scale storm motion, which reaches a steady velocity around 0.7-0.9 m s −1 in the period between 17:45 and 19:30 CET, characterised by the highest rain rates. According to the literature (Ogden et al, 1995;Seo et al, 2012), the downbasin storm velocity may have added to the severity of the storm, giving rise to a stronger flood peak than that of an equivalent stationary storm characterised by the same temporal rainfall distribution and by the same value of 1 .…”
Section: Space-time Rainfall Variability and Storm Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncoupling the precipitation distribution from the parameters of observed events allows for consideration of a great variety of possible patterns. This also applies for the representation of variations in storm motions and storm velocities, which can also strongly influence subsequent PMF estimation (Seo et al 2012, Nikolopoulos et al 2014. Despite this uncoupling, some of the generated distributions are consistent with patterns often observed and correlations in space and time.…”
Section: Discussionmentioning
confidence: 95%
“…The assumptions of homogeneity, stationarity, and randomness in traditional flood frequency studies have been questioned in numerous studies (e.g., Hirschboeck et al, 2000;Jain and Lall, 2001;Milly et al, 2002;Alila and Mtiraoui, 2002;Kwon et al, 2008;Villarini et al, 2009Villarini et al, , 2013Smith et al, 2011;Westra and Sisson, 2011;Vogel et al, 2011;Neiman et al, 2011;Seo et al, 2012;Merz et al, 2014;Lima et al, 2015). To make progress on understanding and mod-response, and large-scale circulation patterns associated with the forecast and diagnosis of rainfall events (Maddox, 1983;Kunkel et al, 1994;Pal and Eltahir, 2002;Schumacher and Johnson, 2005;Amengual et al, 2007;Viglione et al, 2010;Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%